Optimization of Bioethanol Production by Enzymatic Hydrolysis and Fermentation From Rind Cocoa Fruit (Theobroma Cacao L) - Karim, Abd.; Permatasari, Nur Umriani; Ananda, St. Namira (Universitas Negeri Semarang, 2023)
Cocoa (Theobroma cacao L) production in Indonesia based on data from the Central Statistics Agency (BPS) for 2020 reached 720.66 thousand tons and continues to increase every year. Increasing cocoa production can cause cocoa waste to increase as well. Cocoa waste handling can be overcome by producing bioethanol as a way to reduce the amount of waste produced. This study aims to utilize cellulose compounds from cocoa fruit waste in the production of bioethanol through several stages, namely delignification, enzymatic hydrolysis by cellulase enzymes and the fermentation process with the help of Zymomonas mobilis bacteria. The results showed that the lignin level decreased by 19.5%, the hemicellulose level decreased by 6.87% and the cellulose level increased by 27.45%. Hydrolysis and fermentation stages were analyzed using the response surface method (RSM) to obtain optimum conditions. Cellulose can be optimally hydrolyzed using a pH buffer of 2 and a temperature of 30°C with a glucose concentration of 21,703 mg/mL. The fermentation process can be carried out at optimum conditions using a fermentation medium pH 10 with an incubation time of 168 hours. The bioethanol level was analyzed using a refractometer and gas chromatography (GC) with a yield of 8.43% (v/v).